Fishing village; Maracas Bay, Trinidad, B.W.I. - (:unkn) unknown (Wilson and Johnstone, Trinidad; Printed in Scotland by Robert MacLehose and Co.Ltd, 2009)
A scene of a fishing village in Maracas, Trinidad. Postcard number J252.
Colour: Black and white; Style: Portrait; Other: Unbordered, Divided
Keywords: Postcards; Trinidad and Tobago; Fishing villages--Trinidad and Tobago; Bays--Trinidad and Tobago; Huts--Trinidad and Tobago